EFFECT OF HCG APPLICATION IN MALES FROM DIFFERENT VARIETIES OF NILE TILAPIA OREOCHROMIS NILOTICUS - Souza, U. N.; Felizardo, V. O.; Melo, C. C. V.; Reis Neto, R. V. [UNESP]; Machado, M. R. F.; Freitas, R. T. F. (Inst Zootecnia, 2018)
This study evaluated the effect of time of application of human chorionic gonadotropin (hCG) on the reproductive performance of 40 males of of Nile tilapia males from varieties GIFT and UFLA. The experiment was conducted at the Water Recirculation Laboratory of the Fish Farm Station, Department of Animal Science, Federal University of Lavras - MG. The experiment was completely randomized design, in a 2 x 4 factorial scheme (two varieties and four hCG application periods) with five replicates. Twenty males of the GIFT variety and 20 males of the UFLA variety, with microchips, were housed in a water recirculation system. The application periods were at 6 a.m. 12 a.m., 6 p.m. and 12 p.m.. The hCG dosage was performed in a single dose. The following variables were analyzed: sperm motility rate and duration, sperm morphology, semen volume and semen sperm concentration. The obtained data were submitted to variance analyses and the averages were compared by the SNK test at 5% of significance. The period of application and the variety used did not influence the analyzed variables, however the UFLA variety showed a larger number of animals that spermized. The concentration presented an average of 5.73 x 10(5) sperm/mL for the UFLA variety and 4.71 x 105 sperm/mL for the GIFT variety. The volume of semen found for GIFT was 0.9 mL whereas for UFLA it was 0.6 mL. The sperm motility was 96.5% with a duration of 4.33 minutes for the UFLA variety and 88.4% with a duration of 4.8 minutes for the GIFT variety. The number of normal sperm cells presented an average of 86.35% for the UFLA variety and 86.46% for the GIFT variety. Induction with hCG at different periods of application did not present significant difference on the sperm quality parameters of tilapia males.
Keywords: sperm; spermiation; GIFT; hormonal induce; UFLA